2006
DOI: 10.1191/0961203306lu2289xx
|View full text |Cite
|
Sign up to set email alerts
|

High risk of tuberculosis in systemic lupus erythematosus?

Abstract: The incidence and severity of tuberculosis (TB) in patients with systemic lupus erythematosus (SLE) varies greatly among different series. In addition, prospective data are scarce. The aim of this study is to analyse the frequency and severity of TB in our cohort of lupus patients. We analysed data from a prospective database of a single center cohort of 232 patients with SLE (ACR criteria). Prophylaxis with isoniazid was not regularly administered. We identified all cases of TB diagnosed during 10 years (Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 18 publications
4
49
0
9
Order By: Relevance
“…All the studies reported a significant percentage of extrapulmonary TB, up to 66% in a Hong Kong cohort of 526 SLE patients [17]. The mean duration of SLE up to the development of TB was 4.6 years, although it varied from 2 months to 20 years [14][15][16][17][18][19][20][21][22]. Almost all the series reported cases of documented TB before SLE was diagnosed [17,20,21].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All the studies reported a significant percentage of extrapulmonary TB, up to 66% in a Hong Kong cohort of 526 SLE patients [17]. The mean duration of SLE up to the development of TB was 4.6 years, although it varied from 2 months to 20 years [14][15][16][17][18][19][20][21][22]. Almost all the series reported cases of documented TB before SLE was diagnosed [17,20,21].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, several studies conducted in different countries have also documented an increased susceptibility for TB among SLE patients, especially in the Far East, where TB is endemic [13][14][15][16][17][18][19][20][21][22]. The incidence of TB in these studies varied from 150 to 2,450/100,000 patient-years (among Turkish and Indian SLE patients respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Patients with SLE, especially in TB endemic regions, are susceptible to higher incidence and severity of TB (i.e., increased risk of disseminated disease). 17,18 Moreover, TB infection may be implicated in SLE induction and exacerbation as evidenced by the higher prevalence of antecedent TB infection among SLE patients. 19,20 Clinically, TB and SLE may have similar manifestations such as fever, malaise, weight loss and other overlapping pulmonary and neurological presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Так, в Индии и странах Юго-Восточной Азии встречаемость туберку-леза при СКВ в 7-10 раз превосходит таковую в популя-ции и достигает внушительных значений (табл. 2) [54].…”
Section: микобак териальные инфекцииunclassified